Retornantes internos por covid-19: una mirada desde la desigualdad y la informalidad - Lázaro-Aquino, Teódulo Gerardo (2021)
The study's objectives were: 1) Identify who were the returnees, 2) Analyze the internal return factors and 3) Explain both the dynamics and types of return. For this, the qualitative research method was used, in its narrative design modality. The main information gathering technique was documentary observation (newspapers, magazines, webinars, Internet interviews, among others). It is concluded that, although there were conjunctural elements that favored the phenomenon of return such as quarantine, social isolation, social distancing and the state of emergency, there were two structural triggers: inequality and informality in the country. Likewise, the displacement of returnees due to covid-19, a form of forced migration, would take two main trends: one, it would be return migration when the actors make the final decision to stay in their places of origin and two, of re-migration if they decide return again to their migrant destinations. This depends on the duration of the pandemic, the isolation or social confinement, the state of emergency, but above all on the outcome of the ongoing health, economic and social crisis.